Synthesis of Modified Polyvinyl Pyrrolidone (PVP) Silver Nanoparticles Using Soursop (Annona muricata Linn) Leaf Extract and Its Application as a Heavy Metal Colorimetric Sensor - Yussi Pratiwi; Rizky Amelia; Yusmaniar (Pusat Inovasi Sains, 2024)
This study aims to analyze the characteristics and performance of silver nanoparticles (AgNP) synthesized using soursop leaf extract bioreductor modified with the addition of polyvinyl pyrrolidone (PVP) stabilizer as a colorimetric sensor for heavy metal ions. The synthesis of silver nanoparticles was carried out by reducing AgNO3 using soursop leaf extract (Annona muricata Linn) bioreductor modified with the addition of PVP as stabilizer. The results showed that the optimum synthesis volume ratio of AgNP synthesis was 0.7 mL of soursop leaf extract: 10 mL AgNO3 with the addition of 3% PVP stabilizer. The formation of AgNP was characterized by a change in the color of the solution from yellow to brownish with a surface plasmon resonance peak at a maximum wavelength of 438 nm. Fourier-transform infrared spectroscopy studies showed hydroxyl groups (-OH) and carbonyl groups (C=O) play a role in the reduction process of silver ions. Particle size analysis results demonstrated an average particle size of 71.5 nm with a polydispersity index value of 0.364. The results of the colorimetric analysis showed that the synthesized AgNPs proved to be highly selective towards Cu metal ions.